Pengaruh Retribusi Daerah, Pajak Daerah, DAU serta DAK terhadap Belanja Modal Periode 2019-2023 - Rosa, Olivia; Kurnianingsih, Retno (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
Regional governments play a substantial role in the implementation of public services and development at the regional level. Carrying out these functions requires significant funding. This study aims to examine the influence of local retribution, local taxes, DAU, and DAK on capital expenditures in regencies and cities in Central Java Province. This quantitative study used a population of 29 regencies and 6 cities. The sample consisted of the 2019-2023 APBD reports, with saturated sampling technique. Data analysis was performed through multiple linear regression with SPSS 25 as a testing tool. The study found that local retribution and DAK partially had no significant effect on capital expenditures, while local taxes and DAU had a significant effect on capital expenditures. Simultaneously, local retribution, local taxes, DAU and DAK had a significant effect on capital expenditures.